Co-design of Adaptable Learning Outcomes for Sustainable Food Systems Undergraduate Education - Ebel, Roland; Ahmed, Selena; Valley, Will; Jordan, Nicholas; Grossman, Julie; Byker Shanks, Carmen; Stein, Mary; Rogers, Mary; Dring, Colin (Frontiers in Sustainable Food Systems, 2020)
Higher education institutions are increasingly offering Sustainable Food Systems (SFS) degree programs in response to societal demand for training a professional food systems workforce. As a relatively young field, there is a need for clearly articulated learning outcomes (LOs) for SFS education to define student learning through degree programs, design new programs, and evaluate and modify existing programs. New and established SFS programs are often fragmented over multiple academic departments which impedes the development of a coherent and holistic curriculum for approaching the complexity of food topics. Here, we address these needs through the co-creation of adaptable LOs for Baccalaureate degree-level SFS programs which are aligned to a SFS Signature Pedagogy and based on outcomes-based education towards contributing to a solid conceptual basis for SFS education. The SFS Signature Pedagogy is a framework that can be applied to develop students’ systemic capacities, including holistic and pluralistic ways of understanding sustainability challenges, multi-, inter- and trans-disciplinarity, experiential learning, and collective action projects. Our co-design of LOs was based on qualitative content analysis of existing LOs of established SFS programs, a cross-sectional survey with SFS educators and, refinement of LOs from feedback in an expert panel. This process resulted in the eight adaptable LOs: (1) systems thinking, (2) critical reflection, (3) diverse ways of knowing, (4) practical application, (5) multi-context communication, (6) teamwork, (7) collective action, and, (8) advocacy for SFS. We anticipate the adaptable LOs proposed here to be applicable for diverse student communities and geographic and cultural contexts as well as to provide insight for sustainability-related academic programs towards developing professionals equipped with skills and capacities to address complex challenges.